RECURRENT OVARIAN GRANULOSA CELL TUMORS: DIAGNOSIS AND TREATMENT - A. M. Beishembayev; V. A. Khailenko; N. V. Lyubimova; Yu. G. Payanidi; O. A. Anurova; O. N. Streltsova; K. I. Zhordania (Опухоли женской репродуктивной системы)
Recurrent ovarian granulose cell tumors (OGCT) occur in 20-40% of cases. The low incidence of OGCT and the specific features of their clinical course highly hamper the study of the mechanisms of development of recurrences and the possibilities of timely detection of disease progression and the determination of their optimal treatment policy. Thus, the problem of OGCT needs early diagnosis, monitoring, and treatment to be developed for patients with this type of tumors.